2023
DOI: 10.1038/s41598-023-33665-3
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology mechanism of Scutellarin to inhibit RGC pyroptosis in diabetic retinopathy

Abstract: To investigate the effect of scutellarin (SCU) in diabetic retinopathy (DR) and explore the associated molecular network mechanism. The animal model of DR was established from diabetic mellitus (DM) rats by intraperitoneally injected streptozotocin (STZ) at dosage 55 mg/kg. Meanwhile, SCU was intraperitoneally administrated to protect retina from cell pyroptosis induced by DM, and cell pyroptosis was detected by using HE, Nissl staining, and immunofluorescence recognition. Moreover, the hub gene involving in p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…[ 107 , 108 ] Among all neurons, the RGC is most susceptible to damage, resulting in severe visual impairment. [ 109 ] The early stages of DR were closely associated with increased and decreased neurotransmitters, as evidenced by an increment in glutamate release and a decline in γ-aminobutyric acid release. [ 110 ] Fang found that Berberine potently defended against RGC apoptosis in the retina of rodent diabetic animals, and its defensive effect might be linked to the GABAARs/protein kinase C-α pathway activation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 107 , 108 ] Among all neurons, the RGC is most susceptible to damage, resulting in severe visual impairment. [ 109 ] The early stages of DR were closely associated with increased and decreased neurotransmitters, as evidenced by an increment in glutamate release and a decline in γ-aminobutyric acid release. [ 110 ] Fang found that Berberine potently defended against RGC apoptosis in the retina of rodent diabetic animals, and its defensive effect might be linked to the GABAARs/protein kinase C-α pathway activation.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that scutellarin is a VEGF inhibitor and has the potential to be a therapeutic agent for diabetic microangiopathy. Li et al [ 67 ] found induced DR cell focussing in DM rats, particularly in retinal ganglion cells (RGCs), and found that scutellarin administration significantly inhibited cell focussing in DR and explained the molecular network mechanisms involved.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Finally, excessive potassium efflux and caspase-1 activation lead to pyroptosis by cleavage of gasdermin D [110,120]. A recent study indicates that cell pyroptosis of diabetic retinopathy was found in specifically retinal ganglion cells and a flavonoid extracted from the traditional Chinese medicine, scutellarin protected retinal ganglion cell pyroptosis in diabetic retinopathy in vivo via inhibition of caspase-1, gasdermin D, NLRP3, IL-1β and IL-18 [121]. Ginsenosides are steroid-like saponins and are the main active components of ginseng, a well-known traditional Chinese medicine.…”
Section: Pyroptosis; a New Therapeutic Target For The Treatment Of Di...mentioning
confidence: 99%